Anmeldelser - Kjems, Thorkil (Danish Yearbook of Musicology, 1996)
Review of: Dietrich Buxtehude: Complete Chamber Music Vol. I (7 Sonatas Op. 1) and Vol. II (7 Sonatas Op. 2). John Holloway (violin), Jaap ter Linden (viola da gamba), and Lars Ulrik Mortensen (harpsichord). dacapo CD 8.224003, 8.224004.